2022
DOI: 10.1007/s13187-022-02153-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Beliefs About Colorectal Cancer Screening in Puerto Rico

Abstract: The purpose of this study was to describe the psychosocial factors influencing participation in colorectal cancer screening (CRCS) among Puerto Rican men and women. We conducted seven focus groups in metropolitan and rural areas of Puerto Rico (PR) with men and women (using gender specific groups) aged 50 to 80 years (n = 51) who were non-adherent to CRC guidelines. The focus group guide included questions related to colorectal cancer (CRC) and CRC screening knowledge, attitudes, and beliefs. We analyzed data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This could be due to limited outreach by healthcare providers or cultural barriers that prevent the effective dissemination of information. The contrast with studies reporting low attitudes, such as the one by Colón-López et al [ 37 ], may be attributed to methodological differences, such as sample size and composition. For instance, including older patients who have not previously been screened could skew results toward more negative attitudes.…”
Section: Discussionmentioning
confidence: 75%
“…This could be due to limited outreach by healthcare providers or cultural barriers that prevent the effective dissemination of information. The contrast with studies reporting low attitudes, such as the one by Colón-López et al [ 37 ], may be attributed to methodological differences, such as sample size and composition. For instance, including older patients who have not previously been screened could skew results toward more negative attitudes.…”
Section: Discussionmentioning
confidence: 75%
“…A total of 48 papers were included in this review of the literature. A flow chart of the study selection process is reported in Figure 1 11–58 …”
Section: Resultsmentioning
confidence: 99%
“…Further economic barriers to FOBT based screening included the need for financial support to complete the screening process and taking unpaid time off work 12,13,20–22,27,29–31,52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observed disparities in colorectal cancer screening in the context of PR may be attributed to individual and system-level barriers. Prior studies conducted in PR have highlighted individual barriers to colorectal cancer screening, such as embarrassment, diminished perceived benefits, prevailing fatalism, transportation difficulties (especially in rural areas), limited time, and economic burdens [21]. These individual barriers might have been exacerbated during Hurricanes Irma and Maria, the seismic activity of 2020, and the COVID-19 pandemic, which might reflect these delays in colorectal cancer screening catching up to the 2016 baseline screening rates.…”
Section: Discussionmentioning
confidence: 99%